MOLECULAR MODELING OF VITEOSIN-A, A TRACHEOSPASMOLYTIC COMPOUND ISOLATED FROM N-HEXANE EXTRACT OF THE LEAVES OF Vitex Trifolia L. - Alam, Gemini; Sudarmanto, B.S. Ari; Astuti, Puji; Wahyuono, Subagus (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2002)
Viteosin-A, a tracheospasmolytic compound, was successfully isolated from n-hexane extract of the leaves of Vitex trifolia L. With the concentration of 0.05 and 0.15 mg/ml viteosin-A inhibited a guinea pig tracheal contraction due to histamine (10-7 â€“ 10-3 M) in vitro by 27.1 and 47.9 %, respectively. Confirmation of C-5 and C-6 configuration is necessary to determine the active reaction site of viteosin-A and its receptor for future development. This research was focused on a molecular modeling of viteosin-A using computational method with HyperChem Pro 4.0 for Windows as software. Based on spectroscopic data and molecular modeling, viteosin-A has S configuration at C-5 and C-6, and therefore was confirmed as (5S,10S)-6S-acetoxy-8R-methyl-9ï¡-hidroxy-labda-13Z-en-16,15-olide.Keywords: viteosin-A, molecular modeling